'What about the coffee break?' Designing virtual conference spaces for conviviality. Issue 2 (9th November 2022) - Bastian, Michelle; Flatø, Emil Henrik; Baraitser, Lisa; Jordheim, Helge; Salisbury, Laura; van Dooren, Thom
Abstract: Geography, like many other disciplines, is reckoning with the carbon intensity of its practices and rethinking how activities such as annual meetings are held. The Climate Action Task Force of the American Association of Geographers (AAG), for example, was set up in 2019 and seeks to transform the annual conference in light of environmental justice concerns. Mirroring shifts in geographic practice across the globe, these efforts point to a need to understand how new opportunities for knowledge production, such as online events, can operate effectively. In this paper, we offer suggestions for best practice in virtual spaces arising from our Material Life of Time conference held in March 2021, a two‐day global event that ran synchronously across 15 time zones. Given concerns about lack of opportunities for informal exchanges at virtual conferences, or the 'coffee break problem', we designed the event to focus particularly on opportunities for conviviality. This was accomplished through a focus on three key design issues: the spatial, the temporal, and the social. We review previous work on the benefits and drawbacks of synchronous and asynchronous online conference methods and the kinds of geographic communities they might support. We then describe our design approach and reflect on its effectiveness via a variety of feedback materials. We show that our design enabled high delegate satisfaction, a sense of conviviality, and strong connections with new colleagues. However, we also discuss the problems with attendance levels and external commitments that hampered shared time together. We thus call for collective efforts to support the 'event time' of online meetings, rather than expectations to fit them around everyday tasks. Even so, our results suggest that synchronous online events need not result in geographical exclusions linked to time‐zone differences, and we outline further recommendations for reworking the spacetimes of the conference. Short Abstract: Online conferences provide one avenue for potentially reducing academia's carbon footprint. Their widespread take up is accompanied by concerns that they cannot provide adequate alternatives to the face‐to‐face, particularly in terms of building new networks. This paper reports on The Material Life of Time conference and the success of our efforts to plan explicitly for conviviality.